Microstructure, characterizations, functionality and compressive strength of cement-based materials using zinc oxide nanoparticles as an additive - Nochaiya,T. (Elsevier BV, 2015)
© 2014 Elsevier B.V. All rights reserved. Zinc oxide nanoparticles as a nanophotocatalyst has great potential for self-cleaning applications in concrete structures, its effects on the cement hydration, setting time and compressive strength are also important when using it in practice. This paper reports the effects of zinc oxide nanoparticles, as an additive material, on properties of cement-based materials. Setting time, compressive strength and porosity of mortars were investigated. Microstructure and morphology of pastes were characterized using scanning electron microscope and X-ray diffraction (XRD), respectively. Moreover, thermal gravimetric analysis (TGA) and Fourier-transform infrared spectrometer (FTIR) were also used to determine the hydration reaction. The results show that Portland cement paste with additional ZnO was found to slightly increase the water requirement while the setting time presented prolongation period than the control mix. However, compressive strength of ZnO mixes was found to be higher than that of PC mix up to 15% (at 28 days) via filler effect. Microstructure, XRD and TGA results of ZnO pastes show less hydration products before 28 days but similar at 28 days. In addition, FTIR results confirmed the retardation when ZnO was partially added in Portland cement pastes.